Phenothiazine‐Based Oligo(p‐phenylenevinylene)s: Substituents Affected Self‐Assembly, Optical Properties, and Morphology‐Induced Transport. Issue 50 (7th August 2018) - Arivazhagan, C.; Satapathy, Sitakanta; Jana, Arijit; Malakar, Partha; Prasad, Edamana; Ghosh, Sundargopal
Abstract: Designing intramolecular charge‐transfer (ICT)‐based luminogenic ordered assemblies exhibiting significant electrical transport is a challenging task in the field of organic optoelectronics. In this context, a series of novel phenothiazine‐based oligo( p ‐phenylenevinylene) (OPV1 ‐6 ) derivatives were designed and their structure–property relationship was investigated. Upon examining their photophysical properties, all the OPVs were found to exhibit significant intramolecular charge‐transfer characteristics in organic solvents. While inspecting the self‐assembly behaviour, the OPV with a long alkyl chain on the central phenyl core (OPV4 ) underwent gelation in organic solvent mixtures through strong hydrophobic interactions of the long hexadecyl chains and π‐interactions from their aromatic counterparts. Computational studies revealed a lamellar packing of molecules in the assembly. Interestingly, the degree of ICT and the gelation abilities of OPVs were significantly influenced by the electronic nature of the substituents appended to the peripheral phenothiazines. Further, the AC impedance results revealed an increase in storage and electronic transport for the fluorescent thin films prepared by an increase in the content ofOPV4 in PMMA. Abstract : Organogels : A series of phenothiazine‐based oligo(phenylenevinylene) derivatives show intriguing optical properties with intramolecular charge‐transfer characteristics. The long alkyl chain OPVs without bulky substituents at the periphery led to gelation in a mixture of organic solvents. The gels undergo monolayer lamellar assembly revealing the formation of hierarchically ordered 1D fibers (see figure).